American Pluralism : Artists at The Ohio State University. - Antwerp; London; Glasgow; Oslo; Helsinki; Budapest; Dresden; Barrett, Terry (Columbus : College of the Arts, The Ohio State University, 1992)
Heimdall, Georg ; Mendoza, Tony ; Horrell, Deborah ; West, Pheoris ; Shay, Bob ; Slaughter, Todd ; Shineman, Larry ; Nelson, Ardine ; Cochran, Malcolm ; Roth, Richard ; Dallas-Swann, Susan
Antwerp, November 1992 ; London, January 1993 ; Glasgow, March 1993 ; Oslo, May 1993 ; Helsinki, September 1993 ; Budapest, November 1993 ; Dresden, January 994
kunstcatalogus